Critical levels and nutrient sufficiency ranges derived from methods for assessing the nutritional status of oil palm - Matos, Gilson Sergio Bastos de; Fernandes, Antonio Rodrigues; Wadt, Paulo Guilherme Salvador (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to determine critical levels and nutrient sufficiency ranges for oil palm (Elaeis spp.), using methods for assessing the nutritional status of the plants. The methods of mathematical chance (ChM), diagnosis and recommendation integrated system (DRIS), and compositional nutrient diagnosis (CND), besides the critical level obtained by the reduced normal distribution (DNR), were used in productivity data and in nutrient content of 144 leaf samples of oil palm plantations in the state of Pará, Brazil. The regressions of the DRIS and CND indexes with leaf nutrient contents were all significant, and the lowest coefficient of determination was found for N. The sufficiency range intervals obtained with the ChM, DRIS, and CND methods in the nutritionally balanced stands were, in general, narrower than the ones reported in the literature, with few concordant diagnostics, mainly for K. The critical levels obtained with DNR were within the nutritional range intervals obtained with the other methods. ChM, DRIS, CND, and DNR are suited methods for obtaining nutritional reference values, and they indicated N, Ca, S, Mn, and Zn as the nutrients with the highest frequency of deficiency in the evaluated oil palm orchards.